ANALISIS PENGARUH KEMAMPUAN KERJA DAN PENGALAMAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. PRUDENTIAL LIFE ASSURANCE RANTAUPRAPAT - Elida Florentina Sinaga Simanjorang (LPPM Universitas Labuhanbatu, 2020)
This study aims to analyze the effect of work ability and work experience on employee job satisfaction at PT. Prudential Life Assurance Rantauprapat. The subjects of this study were employees of PT. Prudential Life Assurance Rantauprapat with a population of 40 people. The sampling technique used was total sampling, in which the entire population was the research sample. The data collection technique was done by using questionnaires, interviews and observations. The data analysis technique used is multiple linear regression and hypothesis testing (t-test and F test). The results of this study obtained the regression equation Y = 1.677 + 0.633 X1 + 0.311 X2 + e. The results of the t-test show that partially work ability has a positive and significant effect on job satisfaction with a tcount of 4.822> t table 1.687 with a significant value of 0.00ttable 1.687 with a significant value of 0.035